2020
DOI: 10.3389/fonc.2020.00391
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiological Characteristics and Prognostic Factors of Low-Grade Brainstem Glioma: A Real-World Study of Pediatric and Adult Patients

Abstract: Purpose: Our current understanding of low-grade brainstem glioma (LGBSG) is still limited. This study aimed to conduct a large-scale population-based real-world study to understand the epidemiological characteristics of LGBSG and determine the predictive factors of cancer-specific survival (CSS) and overall survival (OS) of LGBSG patients. Patients and Methods: We used Surveillance Epidemiology and End Results database to conduct this study of patients with histologically confirmed LGBSG. Patient demographics,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…Children and adolescents (0-19 years old) accounted for 34.3% of all patients, and more than half of the patients were adults. The predominance of white patients was also very significant in our study, which is consistent with the findings of other cohort studies of gliomas based on the SEER program (13,16). Males and females are almost equally affected.…”
Section: Discussionsupporting
confidence: 92%
“…Children and adolescents (0-19 years old) accounted for 34.3% of all patients, and more than half of the patients were adults. The predominance of white patients was also very significant in our study, which is consistent with the findings of other cohort studies of gliomas based on the SEER program (13,16). Males and females are almost equally affected.…”
Section: Discussionsupporting
confidence: 92%
“…Many previous studies have shown the accurate predictive ability of nomograms for predicting overall survival in patients with low-grade endometrial stromal sarcoma [10], adrenocortical carcinoma [15], hepatoblastoma [16], and many other system cancers. So far, only a few sporadic studies have investigated the straightforward application of nomograms in glioma based on the SEER database [17][18][19][20]. WHO grade II/III glioma is a relatively rare tumour, with no individualized prognostic predictive tool to manage follow-up and aid accurate prognostic assessment.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 10 7 U87/R cells transfected with the si-hsa_circ_0110757 precursor were subcutaneously injected into BALB/c nude mice. When the tumor volume reached 100 mm 3 , TMZ (60 mg/kg) was applied intraperitoneally and tumor volume was measured every 2 days. After 15 days, the whole mice were systemically anesthetized and tumor tissues were collected for RT-PCR, western blot, and immunofluorescence assays.…”
Section: Treatment Of Xenograft-bearing Micementioning
confidence: 99%
“…Glioma, originating from the neuroepithelium and accounting for 40–50% of intracranial tumors, is the most common malignant tumor of the central nervous system 1 , 2 . The main characteristics are diffuse invasive growth of tumor cells, unclear boundaries, relatively unlimited proliferation, and high invasiveness, all of which seriously affect human health 3 . Despite advances in the treatment of gliomas, the 5-year survival rate of glioma patients remains low 4 .…”
Section: Introductionmentioning
confidence: 99%